Governance and Trade in Fresh Vegetables: The Impact of UK Supermarkets on the African Horticulture Industry - Dolan, C; Humphrey, J (Edward Elgar, 2009)
Production of fresh vegetables for export has grown rapidly in a number of countries in sub-Saharan Africa over the last decade. This trade brings producers and exporters based in Africa together with importers and retailers in Europe. Large retailers in Europe play a decisive role in structuring the production and processing of fresh vegetables exported from Africa. The requirements they specify for cost, quality, delivery, product variety, innovation, food safety and quality systems help top determine what types of producers and processors are able to gain access to the fresh vegetables chain and the activities they must carry out. The control over the fresh vegetables trade exercised by UK supermarkets has clear consequences for inclusion and exclusion of producers and exporters of differing types, and for the long-term prospects for the fresh vegetables industry in the two major exporting countries studied, Kenya and Zimbabwe.